2020
DOI: 10.21203/rs.3.rs-64903/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Excretion of urine extracellular vesicles bearing markers of activated immune cells and calcium/phosphorus physiology differ between calcium kidney stone formers and non-stone formers

Abstract: Backgrounds: Previous studies have demonstrated that excretion of urinary extracellular vesicles (EVs) from different nephron segments differs between kidney stone formers and non-stone formers (NSFs), and could reflect pathogenic mechanisms of urinary stone disease. In this study we quantified selected populations of specific urinary EVs carrying protein markers of immune cells and calcium/phosphorus physiology in calcium stone formers (CSFs) compared to non-stone formers (NSFs). Methods Incident CSFs (n = … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…However, CD68 gene expression did not differ between nonstone formers and stone formers (19). A recent study published by our group demonstrated that urinary excretion of CD68-positive extracellular vesicles (derived from activated M1 macrophages) was significantly lower in stone formers compared with nonstone formers, suggesting greater intrarenal expression of proinflammatory macrophages and their vesicles within stone formers (30). In addition, experiments using a hyperoxaluric experimental mouse model demonstrated that daily intra-abdominal administration of IL-4 and IL-13 and transfusion of CD206-positive macrophages increased intrarenal M2 macrophage accumulation and suppressed calcium oxalate crystal formation compared with a control group (25).…”
Section: Discussionmentioning
confidence: 98%
“…However, CD68 gene expression did not differ between nonstone formers and stone formers (19). A recent study published by our group demonstrated that urinary excretion of CD68-positive extracellular vesicles (derived from activated M1 macrophages) was significantly lower in stone formers compared with nonstone formers, suggesting greater intrarenal expression of proinflammatory macrophages and their vesicles within stone formers (30). In addition, experiments using a hyperoxaluric experimental mouse model demonstrated that daily intra-abdominal administration of IL-4 and IL-13 and transfusion of CD206-positive macrophages increased intrarenal M2 macrophage accumulation and suppressed calcium oxalate crystal formation compared with a control group (25).…”
Section: Discussionmentioning
confidence: 98%